2014
DOI: 10.1002/2013je004550
|View full text |Cite
|
Sign up to set email alerts
|

Global climate modeling of the Martian water cycle with improved microphysics and radiatively active water ice clouds

Abstract: Water ice clouds play a key role in the radiative transfer of the Martian atmosphere, impacting its thermal structure, its circulation, and, in turn, the water cycle. Recent studies including the radiative effects of clouds in global climate models (GCMs) have found that the corresponding feedbacks amplify the model defaults. In particular, it prevents models with simple microphysics from reproducing even the basic characteristics of the water cycle. Within that context, we propose a new implementation of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
260
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(270 citation statements)
references
References 45 publications
9
260
0
1
Order By: Relevance
“…This combination allows improvements to be made in the calculations of nucleation, growth and sedimentation, while keeping the computing time low when calculating global transport. A combined scheme such as this has been used in a mesoscale model to study mountain-induced vertical transport of water (Michaels et al 2006), and in a GCM to study equatorial water ice deposits (Nelli et al 2009), clouds and fogs observed by Phoenix (Nelli et al 2010) and the complete hydrological cycle with radiatively active clouds (Navarro et al 2014). The results of such simulations match well with available spacecraft data.…”
Section: Cloud Microphysics and Modellingmentioning
confidence: 70%
“…This combination allows improvements to be made in the calculations of nucleation, growth and sedimentation, while keeping the computing time low when calculating global transport. A combined scheme such as this has been used in a mesoscale model to study mountain-induced vertical transport of water (Michaels et al 2006), and in a GCM to study equatorial water ice deposits (Nelli et al 2009), clouds and fogs observed by Phoenix (Nelli et al 2010) and the complete hydrological cycle with radiatively active clouds (Navarro et al 2014). The results of such simulations match well with available spacecraft data.…”
Section: Cloud Microphysics and Modellingmentioning
confidence: 70%
“…Following analyses by Haberle et al (1999) and Colaprete et al (1999), new models (Hinson and Wilson 2004;Madeleine et al 2012) have considered the radiative effect of these clouds, which in some cases can generate temperature inversions. A further improved 3D GCM model has been developed by Navarro et al (2014), including the nucleation on dust particles, ice particle growth in a supersaturated atmosphere, and scavenging of dust particles due to ice condensation. This study illustrates the importance of microphysics in the modeling of the water cycle.…”
Section: Detection Of H 2 O and Variability In Abundancementioning
confidence: 99%
“…9). (Navarro et al 2014) and observed by the TES instrument aboard MGS. Top water vapor column density; bottom cloud opacity.…”
Section: Detection Of H 2 O and Variability In Abundancementioning
confidence: 99%
See 2 more Smart Citations